2021
DOI: 10.3390/cancers13246354
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of PI3K/AKT Pathway-Related Genes Predicts Outcome in Patients with Pancreatic Cancer: A Comprehensive Bioinformatics-Based Study

Abstract: Pancreatic cancer (PCA) is one of the most lethal malignancies worldwide with a 5-year survival rate of 9%. Despite the advances in the field, the need for an earlier detection and effective therapies is paramount. PCA high heterogeneity suggests that epigenetic alterations play a key role in tumour development. However, only few epigenetic biomarkers or therapeutic targets have been identified so far. Here we explored the potential of distinct DNA methylation signatures as biomarkers for early detection and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
(155 reference statements)
1
3
0
Order By: Relevance
“…For instance, the subgroup with the best clinical outcome (subgroup number 1), was characterized by the highest DNAm age and no tumor recurrence or reported death whatsoever. This phenotype seemed to be associated with the repression of the PI3K-AKT signaling pathway through hypermethylation, which is in line with previous studies in silico (22). Nevertheless, it would be very interesting to confirm whether this repression significantly reduces protein levels and whether that could be somehow related to the increase in DNAm age observed in this subgroup.…”
supporting
confidence: 88%
“…For instance, the subgroup with the best clinical outcome (subgroup number 1), was characterized by the highest DNAm age and no tumor recurrence or reported death whatsoever. This phenotype seemed to be associated with the repression of the PI3K-AKT signaling pathway through hypermethylation, which is in line with previous studies in silico (22). Nevertheless, it would be very interesting to confirm whether this repression significantly reduces protein levels and whether that could be somehow related to the increase in DNAm age observed in this subgroup.…”
supporting
confidence: 88%
“…Moreover, the dysregulation of the cell cycle is also one of the important causes of tumor cell progression. Study of Faleiro et al demonstrated that the methylation of specific genes of PI3K-Akt signaling pathway is responsible for the recurrence and prognosis of pancreatic cancer 41 . All of these indicate a significant relationship between NKCMGS and the occurrence and development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that epigenetic alterations are as crucial as genetic mutations in dysregulating PAM signaling pathway in different types of cancer [181][182][183][184]. In particular, DNA methylation [185], histone post-translational modifications [186], and non-coding RNAs modulation [187,188], are three main epigenetic mechanisms that affect PAM pathway and have been associated with cancer.…”
Section: Epigenetic Regulation Of Pam Pathway In Cancermentioning
confidence: 99%